2015
DOI: 10.7717/peerj.826
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of soil biota groups to plant litter decomposition as mediated by soil use

Abstract: Plant decomposition is dependant on the activity of the soil biota and its interactions with climate, soil properties, and plant residue inputs. This work assessed the roles of different groups of the soil biota on litter decomposition, and the way they are modulated by soil use. Litterbags of different mesh sizes for the selective exclusion of soil fauna by size (macro, meso, and microfauna) were filled with standardized dried leaves and placed on the same soil under different use intensities: naturalized gra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
7
12
0
1
Order By: Relevance
“…The 21 st Century technologies related to DNA sequences revealed that some members of soil biota have no direct or weak relationship with providing functional services to soil medium (Riesenfeld et al, 2004;Bardgett, 2005;Barrios, 2007). This effort helps soil biologists to expand their understanding into many aspects of soil biota, and also to determine how these organisms behave very well in soil environment (Coleman, 2008;Ritz et al, 2010;Castro-Huerta et al, 2015). Taxonomic soil biota provides a linkage to identify some species of soil organisms that are only presence in soil without much support to soil quality and soil management (Riesenfeld et al, 2004).…”
Section: Soil Biota: Functional and Taxonomic Conceptmentioning
confidence: 99%
“…The 21 st Century technologies related to DNA sequences revealed that some members of soil biota have no direct or weak relationship with providing functional services to soil medium (Riesenfeld et al, 2004;Bardgett, 2005;Barrios, 2007). This effort helps soil biologists to expand their understanding into many aspects of soil biota, and also to determine how these organisms behave very well in soil environment (Coleman, 2008;Ritz et al, 2010;Castro-Huerta et al, 2015). Taxonomic soil biota provides a linkage to identify some species of soil organisms that are only presence in soil without much support to soil quality and soil management (Riesenfeld et al, 2004).…”
Section: Soil Biota: Functional and Taxonomic Conceptmentioning
confidence: 99%
“…Remarkably, these organisms play important role in the breakdown and decomposition of many organic materials in soil (Ritz et al, 2010). They contribute widely in the improvement and transformation of soil quality, soil organic matter and soil nutrients availability (Brussaardet al, 2007;Li et al, 2014;Castro-Huerta et al, 2015).Typical examples of biota and their biodiversity are depicted in Figure 9. Table 3 gives the major surface characteristics in the study region.…”
Section: Soil Biota and Biodiversitymentioning
confidence: 99%
“…Protura, Diplura, and Pauropoda are usually less abundant or infrequently detected. Even so, their activities contribute to functions of the microarthropod community with the relative contribution of biotic groups to decomposition changing with disturbance intensity and other environmental factors [15].…”
Section: Introductionmentioning
confidence: 99%